Yousef, Nasser. “Contemporary Modernist Arguments in the Japanese Development Experience: Achievement, Sustainability, and Lessons Learned for Muslims,” Year 14, Issue 53 (Summer 1429 AH/ 2008 CE), Pp. 125 -168. - يوسف ناصر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2008)
Nasser Yousef presents the contemporary modernist arguments that have effectively contributed in drawing the development in Japan. It argues that the contemporary Japanese experience in development has been implemented by elements of the human mind, represented in the political leadership, the figure Emperor, and ambitious people. It aims to direct the attention of researchers in the Muslim world towards this experience to benefit from it. The article discusses features of the contemporary Japanese experience in development, the position of the Muslim world vis-a-vis economic development from an Asian and Confucius perspective, critical observations, development suggestions for a divided Muslim world, and concludes with results of the research and recommendations.